GC-MS ANALYSIS AND ANTILEISHMANIAL ACTIVITY OF DICHLOROMETHANE FRACTION OF ALLIUM CEPA (DFAC) IN VITRO - JAHANGIR KHAN ACHAKZAI; MUHAMMAD ANWAR (International Journal of Pharma and Bio Sciences, 2016)
The GC-MS analysis revealed that dichloromethane fraction Allium cepa (DFAC) consists of 36 compounds which exhibited activity against Leishmania major (DESO). Inhibitory concentrations observed for a dichloromethane fraction of Allium cepa (DFAC) (IC50=70.2 ±3.1 ug/ml). In this bioassay, Amphotericin B (IC50= 0.29 ± 0.05 ug/ml) and pentamidine (IC50=5.09 ±0.09 ug/ml) were used as positive control drugs to compare the parasite inhibition with that by the dichloromethane fraction of Allium cepa (DFAC). This activity was perceived under Incubation period 72 hours and Incubation Temperature 22Cº. Methanol extract of Allium cepa (MEAC), Hexane fraction of Allium cepa (HFAC), Ether fraction of Allium cepa (EFAC), and Diethyl ether fraction of Allium cepa (DEFAC) exhibited no antileishmanial activities.